Partially digital workflow for making complete-arch implant-supported fixed prostheses: A dental technique - Carneiro Pereira, Ana Larisse; Pinto Campos, Maria de Fátima Trindade; Porto de Freitas, Rodrigo Falcão Carvalho; Paiva Tôrres, Ana Clara Soares; de Luna Gomes, Jéssica Marcela [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Porto Carreiro, Adriana da Fonte (Elsevier, 2021)
This article describes a technique for making complete-arch implant-supported fixed prostheses by using intraoral scanning and computer-aided design and computer-aided manufacturing (CAD-CAM) technology for the fabrication of a metal substructure and conventional processing for the prosthesis base. For this, a device was designed to accurately capture the position of multiple implants and the associated digitalized surgical guide, and the metal substructure was planned and milled directly in cobalt-chromium. The color of the gingiva and artificial teeth was selected by using the intraoral scanner software program, and the prosthesis base was processed conventionally. The straightforward methods used to fabricate the prostheses eliminated possible errors associated with conventional substructure casting and occlusal registration.